Pengaruh Penyalutan Terhadap Karakteristik Fisika Kimia dan Stabilitas Tablet Fraksi Etil Asetat Daun Gambir sebagai Agen Antidislipidemia - Yunarto, Nanang; Sulistyowati, Indah; Kurniatri, Arifayu Addiena; Aini, Nurul (Badan Penelitian dan Pengembangan Kesehatan, 2017)
Gambir (Uncaria gambir, Roxb) with the main content of catechin compounds is a major comodity that is efficacious as an antidyslipidemia agent and reduce lesion atheloschlerosis. Catechins are found most often in gambir leaf extract, but are hygroscopic in order to increase the content and its stability is made in the fraction form and formulated in the film-coated tablet preparation. Coatings will protect the gambir from environmental influences. This study aims to find out the best formula of core tablets and film-coated tablets of ethyl acetate fraction of gambir leaf extract. The granulation method used using wet granulation. Optimization of the tablets coating formulation was carried out through three different formulas with the addition of 4, 6, and 8% coatings. The core tablet and the coat were tested for physical characteristics such as weight uniformity, crushed time, hardness, and tablet fragility, chemical characteristics of active substance content and accelerated stability test. The chemical physics evaluation of tablets shows all tablets meeting physical and chemical requirements. Accelerated stability test result obtained catechin content in the core tablets and coat membrane in the absence of loss potency more than 5%. The coated tablet has loss in potency smaller than core tablet. The greater the composition of the coating material used of coating the smaller the loss in potency of catechin content in tablets.AbstrakTanaman gambir (Uncaria gambir, Roxb) dengan kandungan utama senyawa katekin merupakan komoditas unggulan yang berkhasiat sebagai agen antidislipidemia dan mengurangi lesi aterosklerosis. Katekin ditemukan paling banyak pada ekstrak daun gambir, namun bersifat higroskopis sehingga untuk meningkatkan rendemen kandungan dan kestabilannya dibuat dalam bentuk fraksi dan diformulasikan dalam sediaan tablet salut selaput. Penyalut akan melindungi gambir dari pengaruh lingkungan. Penelitian ini bertujuan untuk mengetahui formula terbaik tablet inti dan tablet salut selaput fraksi etil asetat ekstrak daun gambir. Metode granulasi yang digunakan menggunakan granulasi basah. Optimasi formulasi penyalutan tablet dilakukan melalui tiga formula berbeda dengan penambahan bobot bahan penyalut 4, 6, dan 8%. Tablet inti dan salut dilakukan pengujian karakteristik fisika seperti keseragaman bobot, waktu hancur, kekerasan, kerapuhan tablet, karakteristik kimia berupa kadar zat aktif, dan uji stabilitas dipercepat. Evaluasi fisika kimia tablet menunjukkan semua tablet memenuhi persyaratan fisik dan kimia. Hasil uji stabilitas dipercepat diperoleh kandungan katekin dalam tablet inti maupun salut selaput tidak adanya loss in potency yang lebih dari 5%. Tablet salut memiliki loss in potency lebih kecil daripada tablet inti. Semakin besar komposisi bahan penyalut yang digunakan semakin kecil loss in potency kandungan katekin dalam tablet.